Effects of blood flow restriction training on cardiometabolic health and body composition in adults with overweight and obesity: a meta-analysis - Hao Kong; Yilin Zhang; Mingyue Yin; Kai Xu; QingGuo Sun; Yun Xie; Olivier Girard (Frontiers in Physiology)
ObjectiveThis meta-analysis aims to evaluate the effects of blood flow restriction (BFR) training on cardiometabolic health and body composition in adults with overweight and obesity.MethodFollowing PRISMA guidelines, a systematic search of PubMed (MEDLINE), EMBASE, Web of Science, Cochrane, and Scopus databases was conducted on 15 March 2024. Pooled effects for each outcome were summarized using Hedge’s g (g) through meta-analysis-based random effects models, and subgroup analyses were used to explore moderators.ResultsA total of 11 studies with 242 participants (Age:32.6 ± 3.6, BMI:27.2 ± 3.5) were included. Regarding cardiometabolic health, BFR training significantly reduced systolic blood pressure (g = 0.62 [0.08, 1.16], p = 0.02), while no significant differences were observed in maximal oxygen uptake (g = 0.48 [-0.21, 1.17], p = 0.17) or diastolic blood pressure (g = 0.31 [-0.22, 0.84], p = 0.25). Regarding body composition, BFR training significantly reduced body fat percentage (g = 0.30 [0.01, 0.58]; p = 0.04), while no significant differences (p > 0.05) were observed in body weight (g = 0.14 [-0.14, 0.42]), body mass index (g = 0.08 [-0.21, 0.38]), waist circumference (g = 0.13 [-0.28, 0.53]), or waist-to-hip ratio (g = 0.48 [-0.19, 1.15]). Subgroup analysis revealed no significant difference in improving systolic blood pressure (g = 0.57 [-0.10, 1.24] vs. g = 0.70 [-0.18, 1.59]) and body fat percentage (g = 0.20 [-0.20, 0.61] vs. g = 0.45 [-0.05, 0.95]) between BFR resistance training and BFR aerobic training. In all selected studies, the overall risk of bias was categorized as “some concern”. The certainty of evidence for the BFR outcomes was low.ConclusionBFR training shows promise in improving cardiometabolic health and body composition, indicating that it may serve as a beneficial, individualized exercise prescription for improving cardiovascular disease risk and fat loss in adults with excess body weight and obesity.Systematic Review Registration:https://archive.org/details/osf-registrations-uv6jx-v1.